Numerical investigation of melting and freezing processes of spherical encapsulated ice ball [electronic resource] - Mohamad Firdaus Abdul Wahab, 1989-; Mohd. Kamal Ariffin, supervisor; Fakulti Kejuruteraan Mekanikal (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012